ANALYSIS OF MACRONUTRIENCONTENT, GLYCEMIC INDEX AND CALCIUM OXALATE ELIMINATION IN Amorphophallus campanulatus (Roxb.) - Endang Lukitaningsih; Rumiyati Rumiyati; Ika Puspitasari; Meti Christiana (Universitas Syiah Kuala, 2012)
Recently, the research to find alternative sources of carbohydrates as a replacement for rice has been developed. Walur is one of the carbohydrate sources that can be explored because it can be grown in any area with out special treatment. However, walur has limitation for direct consumption, because it contains calcium oxalate. The purposes of this study were to determine the chemical character (macronutrient content), calculate glycemic index and get the proper washing techniques to elimin ate calcium oxalate of walur. Macro nutrients content studied in this research include carbohydrates, fats, protein, star chand crude fiber. Analysis of macronutrients has been chemically done, while the glycemic index was measured by in vivo using glucose as a standard. Elimination of calcium oxalate was conducted by washing the fresh walur tubers using a solution of0.01NHCl-NaOH, 5% NaCl, and solution of lemon-lime. The content of oxalate before and after washing was analyzed by permanganometry method. The results showed that walur containing 4.34 ±0.07% of reducingsugar,3.24 ± 0.06 % of not-reducing sugar, 11.27±0.40 % of crude fiber,0.03±1.05 % of starchand0.57±0.01 % of protein. Qualitative analysis of fatty acids showed that hexade canoicacid, octade cadienoicacid, and the acide icosatetranoic were detected in high concentrations. The glycemic index valueof walur was relative lylow, about of 16.9. In addition, washing technique using a solution of lemon-lime was the most excellent technique and can reduce the oxalate content up to61.82%.Fromthis research, it can be concluded that walur can be used as food substitute esrice after washing treatment using lemon-lime solution to remove the calcium oxalate content.